Future Scenarios for IoT Implementation in the Farming Industry - Tan Jia Ho,; Ahmad, Nurazwa; Muhammad Ammar Shafi, (Research in Management of Technology and Business, 2024)
Smart farming is essential for enhancing crop quality and meeting the rapidly increasing global food demand projected until 2050. The growing human population will significantly impact future farming demand and supply. However, IoT technology faces security challenges, particularly when older devices connect to the internet using public networks. This study aims to identify the issues, challenges, and trends of IoT implementation in the farming industry and develop four possible future scenarios. A questionnaire was distributed to 384 farmers, with 124 valid responses, resulting in a 32.3% response rate. The study employs the STEEPV method for analysis, utilizing scenario building to identify study objectives and impact-uncertainty analysis to assess decision-making variables. The leading drivers identified are “IoT provides meaningful farming data” and “IoT helps increase crop production.” These drivers were used to develop four scenarios: ‘Smart Agriculture,’ ‘Doom of Technology,’ ‘Disqualified Technology,’ and ‘Rejected Technology.’ Implementing IoT in future farming can simplify farmers’ tasks and reduce time spent in the field. For all scenarios, collaboration between policymakers and industry stakeholders is essential. Policymakers need to create an enabling environment through supportive policies and regulations, while industry stakeholders must focus on innovation, security, and education to ensure the successful implementation of IoT in farming. By addressing these implications, both groups can help drive the agricultural sector towards a more efficient and sustainable future.